STRATEGI PENGGEMBALAAN REMAJA MELALUI MEDIA SOSIAL - Laheba, Timothy; Hermanto, Yanto (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2024)
The role of information technology in church ministry is becoming increasingly important nowadays. One of the technological developments that is currently widely used in church services is social media. This social media is widely used because it can reach many people very quickly and easily. This research was conducted to understand the strategies that can be used by churches to effectively shepherd the youth generation. The teenage generation is a generation that is very close to social media. The teenage generation is at the stage of searching for identity and is very easily exposed to negative content on social media. This is a reason for the church to be present and provide shepherding through social media to them. This research uses a literature study approach to find four factors that influence the quality of shepherding carried out by churches through social media. These factors are the choice of social media used, content shared, human resources involved and continuous innovation. By paying attention to these four factors, it is hoped that the church will be able to overcome challenges and provide more effective shepherding to the younger generation.